Multiple Myeloma Masquerades as Rheumatic Diseases. (March 2013) - Shen, Michael; Ng, Swee Cheng
Diagnosing rheumatic disease can be challenging because of protean manifestations and unexplained clinical features. We present two cases of multiple myeloma masquerading as rheumatic diseases, and describe how potential misdiagnoses were avoided. The first patient presented with thickened skin, mimicking systemic sclerosis. This was actually multiple myeloma manifesting an extremely rare cutaneous paraneoplastic phenomena; "Scleromyxedema". The second patient presented with acute monocular blindness and high erythrocyte sedimentation rate (ESR), initially misdiagnosed as giant cell arteritis. However, this was also multiple myeloma with hyperviscosity causing blindness. It is important to consider differentials despite fulfilment of conventional criteria or clinical patterns in diagnosing rheumatic disease.